Localized RNAs and their functions. - Ding, D.; Lipshitz, H.D. (BioEssays, 1993)
The eukaryotic cell is partitioned by membranes into spatially and functionally discrete subcellular organelles. In addition, the cytoplasm itself is partitioned into discrete subregions that carry out specific functions. Such compartmentation can be achieved by localizing proteins and RNAs to different subcellular regions. This review will focus on localized RNAs, with a particular emphasis on RNA localization mechanisms and on the possible biological functions of localization of these RNAs. In recent years, an increasing number of localized RNAs have been identified in a variety of cell types among many animal species. Emphasis here will be on localized RNAs in the most intensively studied systems-Drosophila and Xenopus eggs and early embryos.